A Model of Successful Innovation of Local Government Organizations: A Case Study of Thung Hua Chang Subdistrict Municipality, Thung Hua Chang District, Lamphun Province - Setthakorn, Wit; Metasuttirat, Jirawat (Asia Social Issues, 2025)
The purposes of this qualitative research were to investigate the factors affecting the success of implementing the innovation project called “Good School Near Home, Continuing Sufficiency Economy, Integrating Local Way of Life” and to study the development guidelines of the innovation. The study results indicate that the distinctive points of the innovation project of Thung Hua Chang Subdistrict Municipality are the integration of teaching and learning consistent with the local area and the management of support for the school. The success factors in the implementation of the innovation project were as follows. 1) Personal factors: School administrators and local staff are experienced, competent professionals who understand the context of the area 2) Development factors: Focus on new learning methods that make a difference using modern teaching techniques. 3) Administrative factors: An important factor is the decentralization of local government organizations to drive work in the area with policy independence that can effectively develop the school. New findings for approaches to developing local innovation projects were 1) Developing the school curriculum in line with the context and needs of local people. 2) Continuous planning policy of Thung Hua Chang subdistrict municipality. 3) Creating cooperation with networks and local agencies. As for the limitations, the central bureaucratic structure that controls the local authority of the municipality and local schools is quite high, causing development to be limited.